2018
DOI: 10.1111/jpi.12497
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects prepuberal testis from deleterious effects of bisphenol A or diethylhexyl phthalate by preserving H3K9 methylation

Abstract: A growing number of couples experience fertility issues with almost half being due to malefactors. The exposure to toxic environmental contaminants, such as endocrine disruptors (EDs), has been shown to negatively affect male fertility. EDs are present in the environment, and exposure to these toxins results in the failure of spermatogenesis. The deleterious effects of EDs on spermatogenesis have been well documented, whereas improvement of infertility associated with spermatogenesis defects remains a great ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 63 publications
(126 reference statements)
1
32
0
Order By: Relevance
“…Consequently, the ability to interfere with the hormonal axis has been observed, thereby influencing steroid signaling (12). BPA affects testis competence, varying the gene expression of steroid hormone receptors and influencing the enzymes that catalyze DNA methylation, as demonstrated by in vivo and in vitro animal studies (13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Reproductive Endocrine Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the ability to interfere with the hormonal axis has been observed, thereby influencing steroid signaling (12). BPA affects testis competence, varying the gene expression of steroid hormone receptors and influencing the enzymes that catalyze DNA methylation, as demonstrated by in vivo and in vitro animal studies (13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Reproductive Endocrine Systemmentioning
confidence: 99%
“…Another mechanism by which epigenetic changes are induced may be the increase in oxidative stress caused by BPA exposure (18,19); in this sense, an in vitro study from Zhang et al (20) showed that after exposing mouse testicular cells to BPA, the mRNA levels of proteins involved in sexual hormone steroidogenesis as StAR, P450scc, Cyp17a1, and 3β-HSD were reduced but were also normalized after exposure to melatonin. Finally, the exposure to BPA in mouse preimplantation embryo produces a disruption of testicular synthesis of testosterone and reduction of StAR promoter histone acetylation, thereby inducing a retard of testis development (21).…”
Section: Reproductive Endocrine Systemmentioning
confidence: 99%
“…Melatonin appears to be particularly suitable in serving as an environmental sensor [106], given that its secretion is affected by different wavelengths of light [192], temperature [160], altitude [116] and seasonal cycles [85]. Recent literature indicates that melatonin protects spermatogonial stem cells from endocrine disruptors such as bisphenol A or diethylhexyl phthalate by maintaining histone H3K9 dimethylation and promotes their recovery [284]. Similarly, melatonin also protects spermatogonial stem cells in mice from hexavalent chromium, another environmental carcinogen, by preventing trimethylation of histone H3K9 or H3K27, thereby preventing germ cell apoptosis and maintaining fertility [148,287].…”
Section: Epigeneticsmentioning
confidence: 99%
“…Wang et al, 2016;. Lastly, some studies have shown that post-natal exposure to BPA increases the amount of reactive oxygen species (ROS) compromising oocyte maturation and chromosome segregation and inducing DNA damages such as 8-hydroxydeoxyguanosine (8OdG) (Ganesan & Keating, 2016;T. Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%